Campur Kode dalam Interaksi Antarmahasiswa Banggai Kepulauan di Kota Gorontalo - Ne'u, Lusi Oktaviana; Ntelu, Asna; Muslimin, Muslimin (Universitas Negeri Gorontalo, 2023)
The study's formulation was to determine the forms of code mix and the types of code mix in the interaction between Banggai Kepulauan students in Gorontalo City. This study aimed to describe the forms and types of code mix that occur in interactions between Banggai Kepulauan students at the research site. This descriptive qualitative research applied a sociolinguistic theory. The data includes conversation, words, and sentences that depict code-mixing events between Banggai Kepulauan students in the mentioned city. The data collection techniques comprised listening, recording, speaking, and note-taking. Miles and Huberman's data analysis used in this research includes stages; data reduction, data display, and conclusion drawing. The findings and discussion revealed that (1) there are 5 forms of code mix, viz., (a) words, namely 41 data, including words in Banggai language, namely